2015
DOI: 10.1017/s0021859615000386
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plant morphological expression in 12 perennial ryegrass cultivars following frequent and infrequent cutting management

Abstract: SUMMARYPerennial ryegrass (Lolium perenne L.) cultivars are out-breeding populations of differing phenotypes, potentially allowing for directional selection to occur after sowing. To investigate this, the morphology of individual space plants (i.e. isolated plants sown at 0·75 m row spaces) grown from tillers extracted from single-cultivar swards subjected to frequent cutting (FC) or infrequent cutting (IC) for 5 years (aged accessions) were compared with plants grown from seed (seed accessions). The study exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The shorter lamina lengths in the field survivors compared with plants freshly grown from remnant seed that was observed in the first controlled experiment were not unexpected. Cashman, Gilliland, McEvoy, Watson, and O'Donovan (2016) reported that ryegrass cultivars grown from aged swards were smaller than the same cultivar grown from seed. The leaves on ryegrass ecotypes from New Zealand hill pastures were on average 20% shorter than on six ryegrass cultivar controls grown from seed (Wedderburn et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The shorter lamina lengths in the field survivors compared with plants freshly grown from remnant seed that was observed in the first controlled experiment were not unexpected. Cashman, Gilliland, McEvoy, Watson, and O'Donovan (2016) reported that ryegrass cultivars grown from aged swards were smaller than the same cultivar grown from seed. The leaves on ryegrass ecotypes from New Zealand hill pastures were on average 20% shorter than on six ryegrass cultivar controls grown from seed (Wedderburn et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Whether this difference was due to a genetic shift has been studied. Cashman (2014) was not able to distinguish between 'aged' and 'seed' accessions of any plants sampled directly from the 12 cultivars at the Poukawa site assessed in a spaced plant trial in Hamilton. Conversely, O'Connor et al (2020) did identify additive genetic differences associated with grazing avoidance traits between half-sib families generated from plants of 'Grasslands Samson' sourced from Poukawa and their commercially bought seed counterparts in a grazed row field trial undertaken in Palmerston North.…”
Section: Introductionmentioning
confidence: 87%
“…The study found 'Grasslands Samson' was more subject to directional selection. Cashman et al (2016) assessed phenotypic characters of 'aged' and 'seed' accessions of European and New Zealand ('Alto', 'Arrow', and 'Bealey') cultivars in a sown plot field trial in Fermoy, Ireland. They also found the direction and magnitude of change between 'aged' and 'seed' accessions was cultivar dependant.…”
Section: Total Number Of Tillers (Tn)mentioning
confidence: 99%
“…Over time, the selected population may have undergone selection pressure, leading to the development of stronger genotypes that exhibit higher dry matter yields, greater ground cover, increased plant survival, and taller plant height. Adaption of the selected population explains its superior performance in terms of these phenotypic traits [55]. Additionally, the harvesting year was identified as a short-term environmental influence on the expression of plant phenotypic traits.…”
Section: Effect Of the Environment On The Expression Of Pasture Persi...mentioning
confidence: 99%
“…The occurrence and performance of endophytes can be influenced by plant genotype and environmental factors, and the genomic information of endophytes can undergo changes through natural selection [55]. Thus, the observed persistence of perennial ryegrass can be influenced by the interaction between endophytes and the environment and between cultivars and the environment.…”
Section: Interaction Of Cultivar Endophyte and Environmentmentioning
confidence: 99%